2020
DOI: 10.2147/opth.s285818
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rotation Characteristics of Three Toric Monofocal Intraocular Lenses</p>

Abstract: Purpose To evaluate the rotational stability of the three monofocal toric intraocular lenses (IOLs) via data from an online toric IOL back-calculator. Methods A retrospective data review of an online toric IOL back-calculator, which allows users to input preoperative toric planning information, postoperative lens orientation, and subjective refraction. Inputted data were used to determine the optimal orientation of the toric IOL to minimize residual refractive astigmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
14
1
2
Order By: Relevance
“…TECNIS toric IOL of Johnson & Johnson Vision Care, Inc. (Santa Ana, CA) has been regarded to have relatively poor rotational stability with greater amount of misalignment 3 , 4 , 6 , 7 and higher rate of repositioning surgery 5 , 7 . The manufacturer recently modified this toric IOL to be a new version, TECNIS II, by introducing frosted haptics, which are aimed to offer more surface texture and friction between the lens haptics and the capsular bag.…”
Section: Introductionmentioning
confidence: 99%
“…TECNIS toric IOL of Johnson & Johnson Vision Care, Inc. (Santa Ana, CA) has been regarded to have relatively poor rotational stability with greater amount of misalignment 3 , 4 , 6 , 7 and higher rate of repositioning surgery 5 , 7 . The manufacturer recently modified this toric IOL to be a new version, TECNIS II, by introducing frosted haptics, which are aimed to offer more surface texture and friction between the lens haptics and the capsular bag.…”
Section: Introductionmentioning
confidence: 99%
“…Other clinical studies showed that postoperative rotation of Acrysof IOLs is most likely less 37,38], with the long AXL, WTR, and oblique astigmatism being risk factors for toric IOLs rotation [39,40]. TECNIS IOLs have designs and materials similar to those of Acrysof, indicating the presence of a good degree of stability [41]. Hirnschall et al [42] reported that the average rotation of TECNIS IOLs was 3.27 ± 2.37 °.…”
Section: Discussionmentioning
confidence: 99%
“…During an uncomplicated cataract surgery, lens rotation is 1–3° within 24 months of surgery. Kramer et al [ 20 ] observed that in patients with residual astigmatism, 77.4% of cases were due to intraocular lens rotation of ≥5°. The risk of rotation increases if the lens was originally aligned with oblique axes.…”
Section: Discussionmentioning
confidence: 99%